THE ROLE OF ANTI-VEGF THERAPY IN IMPROVING THE EFFICACY OF SURGICAL TREATMENT OF SECONDARY NEOVASCULAR GLAUCOMA - Uliana Sydorchuk; Ihor Novytskyy (Acta Medica Leopoliensia)
Neovascular glaucoma (NVG) is a refractory glaucoma secondary to retinal ischemic diseases.